Impacts of tillage practices on soil carbon stocks in the US corn-soybean cropping system during 1998 to 2016 - Zhen Yu; Chaoqun Lu; David A Hennessy; Hongli Feng; Hanqin Tian (Environmental Research Letters, 2020)
Tillage alters the thermal and wetness conditions in soil, which facilitates soil organic matter oxidation and water transportation, leading to rapid depletion of soil carbon (C). Little is known about tillage intensity change (TIC) and its impacts in the US corn-soybean rotation system over the past two decades. Using time-series tillage maps developed from a private survey and a process-based land ecosystem model, here we examined how tillage intensity has changed across the nation and affected soil organic carbon (SOC) storage from 1998 to 2016. Results derived from the combination of tillage survey data and cropland distribution maps show that total corn-soybean area consistently increased from 62.3 Mha in 1998 to 66.8 Mha in 2008 and to 73.1 Mha in 2016, among which the acreage under no-till system increased from 16.9 Mha in 1998 to 28.9 Mha in 2008, while conservation and conventional tillage decreased by 3.8 and 3.9 Mha, respectively. The extent of no-till practice in corn-soybean lands shrank by 2.6 Mha from 2008 to 2016, while conservation and conventional tillage increased by 2.8 and 6.1 Mha in the same period. Modeling simulations reveal that historical tillage practices led to a soil C loss of 10.3 (spring till only) to 15.2 (tilled in both spring and fall) Tg C yr ^−1 in the study area from 1998 to 2016. In addition, reduced tillage intensity in corn-soybean cropland contributed to SOC accumulation at 1.0 Tg C yr ^−1 (1.6 g C m ^−2 yr ^−1 ) from 1998 to 2008, but the SOC gain was offset by SOC reduction at 2.4 Tg C yr ^−1 (3.4 g C m ^−2 yr ^−1 ) from increased tillage intensity during the period 2008–2016. For both periods, TIC-induced hydrological C loss accounted for 15% of the SOC change, while the rest was attributed to gaseous-C loss.